The ability to create NTD silicon technology in the IRT-T reactor in a horizontal experimental channel with one-side access - Varlachev V. A. Valery Aleksandrovich; Golovathkiy A. V. Aleksey Vasilievich; Emets E. G. Evgeny Gennadievich; Butko Ya. A. Yana Aleksandrovna (2016, 2016)
Title screen